The impact of moral resilience on nurse turnover intentions: the mediating role of job burnout in a cross-sectional study - Lijuan Yi; Zhuomei Chen; María F. Jiménez-Herrera; Xiuni Gan; Yi Ren; Xu Tian (BMC, 2024)
Abstract Background High nursing staff turnover is a critical issue that negatively impacts the quality of care and patient safety. Turnover intentions, a key predictor of actual turnover, reflect an individual's likelihood of leaving their current position. Understanding the underlying mechanisms driving nurse turnover intentions is crucial for developing targeted interventions to stabilize the nursing workforce globally. Objectives This study aims to explore the relationship between moral resilience, job burnout, and turnover intentions among nurses, focusing on the mediating role of job burnout in this relationship. Design This study employed a quantitative, cross-sectional design. Methods A convenience sample of 322 registered nurses was recruited from two tertiary hospitals in China between August and October 2023. Data were collected using the Chinese version of the Rushton Moral Resilience Scale (Chi-RMRS), the Maslach Burnout Inventory (MBI), and the Turnover Intention Scale. Data analyses were conducted using SPSS 26.0 and Amos 21.0. The study followed the STROBE guidelines for observational research. Ethical consideration Before the commencement of data collection, the Institutional Review Board of Hunan Traditional Chinese Medical College (YXLL202401004) granted ethical approval. Results The proposed model exhibited an excellent fit to the data, with fit indices as follows: χ2/df = 1.819, CFI = 0.977, TLI = 0.961, RMSEA = 0.072 (90% confidence interval [CI]: 0.033 to 0.107). The structural equation model revealed that moral resilience was inversely associated with job burnout and turnover intentions. Furthermore, job burnout fully mediated the relationship between moral resilience and turnover intentions (β = −0.473, p = 0.007). Further analysis indicated that the depersonalization component of job burnout was the sole mediator in the relationship between moral resilience and turnover intention (β = -3.934, 95% CI [-5.837, -1.932]). Conclusion The findings indicate that moral resilience among nurses is negatively associated with turnover intentions, with this effect fully mediated by the depersonalization dimension of job burnout. Enhancing moral resilience in nurses may be valuable strategy for healthcare administrators to mitigate job burnout and subsequently reduce turnover intentions.